Penerapan Regresi Linear Berganda Pada Perubahan Kecepatan Aliran Dan Kehilangan Energi Akibat Kemiringan Dasar Saluran Terbuka - Sumayyah An Nafiah; Fauziah Latif; Muh. Agussalim (Jurnal Karajata Engineering, 2026)
The slope of the channel bed affects the flow velocity and the amount of energy loss due to gravity. This study aims to analyze the effect of the channel bed slope on flow velocity and energy loss, and to develop an energy loss prediction model. The slope variations used were 1°, 2°, and 3°. The test results showed that a slope of 3° produced the highest flow velocity, namely 2.177 m/s, with an energy loss of 0.261, while a slope of 1° produced a flow velocity of 0.597 m/s and an energy loss of 0.028. The multiple linear regression model produced the equation Y = −0.0133 + 0.016X₁ + 1.395X₂, which indicates that flow velocity and water level have a positive effect on energy loss. This model can be used to estimate energy loss based on channel hydraulic parameters.